2018
DOI: 10.13189/aeb.2018.060201
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Knowledge Management and Organizational Performance of Malaysian Private Colleges: A Mediating Role of Managing Talent Practices

Abstract: Knowledge management plays a vital role in sustaining organizational performance of private academic institutions over time. Nonetheless the linkage between knowledge management, managing talent practices and organizational performance is not adequately addressed. This study therefore is aimed to investigate the relationship between knowledge management and organizational performance of Malaysian private colleges and whether managing talent practices, namely managing talent development and talent retention med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They argued that employee development tends to be much more effective than recruitment in increasing human capital. Similarly, Keat and Lin [61] found that talent development has a mediating effect between knowledge management and organizational performance in Malaysian private colleges. They added that employee development is more important than retention management, as their findings found no support that talent retention has a mediating factor between knowledge management and organizational performance.…”
Section: Knowledge-based Training and Developmentmentioning
confidence: 88%
“…They argued that employee development tends to be much more effective than recruitment in increasing human capital. Similarly, Keat and Lin [61] found that talent development has a mediating effect between knowledge management and organizational performance in Malaysian private colleges. They added that employee development is more important than retention management, as their findings found no support that talent retention has a mediating factor between knowledge management and organizational performance.…”
Section: Knowledge-based Training and Developmentmentioning
confidence: 88%